Near infrared spectroscopy detection of hemispheric cerebral ischemia following middle cerebral artery occlusion in rats. (January 2023) - Wong, Ardy; Bhuiyan, Mohammad Iqbal Hossain; Rothman, Jeffrey; Drew, Kelly; Pourrezaei, Kambiz; Sun, Dandan; Barati, Zeinab
Abstract: Timely and sensitive in vivo estimation of ischemic stroke-induced brain infarction are necessary to guide diagnosis and evaluation of treatments' efficacy. The gold standard for estimation of the cerebral infarction volume is magnetic resonance imaging (MRI), which is expensive and not readily accessible. Measuring regional cerebral blood flow (rCBF) with Laser Doppler flowmetry (LDF) is the status quo for confirming reduced blood flow in experimental ischemic stroke models. However, rCBF reduction following cerebral artery occlusion often does not correlate with subsequent infarct volume. In the present study, we employed the continuous-wave near infrared spectroscopy (NIRS) technique to monitor cerebral oxygenation during 90 min of the intraluminal middle cerebral artery occlusion (MCAO) in Sprague-Dawley rats (n = 8, male). The NIRS device consisted of a controller module and an optical sensor with two LED light sources and two photodiodes making up two parallel channels for monitoring left and right cerebral hemispheres. Optical intensity measurements were converted to deoxyhemoglobin (Hb) and oxyhemoglobin (HbO2 ) changes relative to a 2-min window prior to MCAO. Area under the curve (auc) for Hb and HbO2 was calculated for the 90-min occlusion period for each hemisphere (ipsilateral and contralateral). To obtain a measure of total ischemia, auc of the contralateral side was subtracted from the ipsilateral side resulting in ΔHb and ΔHbO2 parameters. Infarct volume (IV) was calculated by triphenyl tetrazolium chloride (TTC) staining at 24h reperfusion. Results showed a significant negative correlation (r = −0.81, p = 0.03) between ΔHb and infarct volume. In conclusion, our results show feasibility of using a noninvasive optical imaging instrument, namely NIRS, in monitoring cerebral ischemia in a rodent stroke model. This cost-effective, non-invasive technique may improve the rigor of experimental models of ischemic stroke by enabling in vivo longitudinal assessment of cerebral oxygenation and ischemic injury. Highlights: Middle cerebral artery occlusion surgery was performed to induce stroke. A miniaturized Near Infrared Spectroscopy device was used for quantitative in vivo estimation of the brain infarction. We found that the final infarct volume is correlated with deoxygenation on the contralateral hemisphere.